Ефекти гетерополіядерного комплексу перехідних металів РО39 в імунній системі мишей - Семесюк, Н.І.; Рудик, М.П.; Позур, В.В.; Сківка, Л.М.; Позур, В.К.; Кокозей, В.М. (Видавничий дім "Академперіодика" НАН України, 2008)
The effect of a heteropolynuclear complex of transition metals PO39 on indices of the immunological reactivity of mice is investigated. PO39 injected in belly cavity causes a decrease of cytomorphologic characteristics of immune system organs with increase in the amount of liver mononuclear leucocytes of mice. The intramuscular injection of PO39 was not shown trustworthy changes of the immunological reactivity of mice.